2009
DOI: 10.1111/j.1365-2265.2008.03471.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial vasopressin‐sensitive ACTH‐independent macronodular adrenal hyperplasia (VPs‐AIMAH): clinical studies of three kindreds

Abstract: Adrenal nodules, suppressed ACTH and increased VP sensitivity may represent preclinical disease, allowing early detection, and treatment, of affected individuals. In AIMAH-01, increased VP sensitivity may be due to adrenal VP receptor overexpression. In these kindreds, VPs-AIMAH is familial, and autosomal dominant inheritance is most likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 35 publications
0
33
0
11
Order By: Relevance
“…A French family with BMAH was found to have aberrant 5-HT 4 and vasopressin adrenal receptors in three siblings (two females of 54 and 56 years old, and one 57-year-old male) and their 81-year-old father (9). Very recently, in an Australian kindred carrying an ARMC5 mutation, vasopressin-responsive BMAH was present in seven members of the family (23); two other Australian BMAH families with partial endocrine investigation suggested vasopressin responsiveness in a father and a son in one family, and in three siblings in the second family (10). In contrast to the family in this study, these authors found no correlations between DST or vasopressin and the diagnosis of BMAH ascertained by adrenal imaging.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…A French family with BMAH was found to have aberrant 5-HT 4 and vasopressin adrenal receptors in three siblings (two females of 54 and 56 years old, and one 57-year-old male) and their 81-year-old father (9). Very recently, in an Australian kindred carrying an ARMC5 mutation, vasopressin-responsive BMAH was present in seven members of the family (23); two other Australian BMAH families with partial endocrine investigation suggested vasopressin responsiveness in a father and a son in one family, and in three siblings in the second family (10). In contrast to the family in this study, these authors found no correlations between DST or vasopressin and the diagnosis of BMAH ascertained by adrenal imaging.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Rarely, CS is secondary to primary bilateral adrenal hyperplasias (!2%), and this includes primary bilateral macronodular adrenal hyperplasia (BMAH) (2). Most BMAH cases were initially reported as sporadic, but more than ten kindreds of familial BMAH were reported in recent years, and in all cases their presentation suggested an autosomal dominant mode of transmission (3,4,5,6,7,8,9,10). The true prevalence of hereditary BMAH may have been underestimated because familial screening was not performed systematically (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, several reports of familial cases with autosomal dominant transmission patterns have been published suggesting germline genetic etiology (32,77,78,79,80,81,82,83). In familial BMAH without other genetic syndrome (such as MEN-1, polyposis coli), specific aberrant GPCR including vasopressin, b-adrenergic and HT4 receptors were found in all members from the same family; in contrast, in one large Brazilian family, the pattern of aberrant receptors varied between the different affected members (27,32,77,78,79,80,81,82,83). The relation between ARMC5 mutation and aberrant GPCR has not been examined in detail yet.…”
Section: Aberrant Gpcr In Familial Cases Of Bmahmentioning
confidence: 99%
“…The great originality in PBMAH resides in the cortisol response to non-physiological stimuli, giving birth to the concept of illegitimate membrane receptors in adrenocortical cells. Various stimulating ligands, binding to protein G-coupled receptors were described, including glucose-dependent insulinotropic peptide (GIP) responsible for food-dependent Cushing syndrome (Reznik et al 1992), LH/HCG responsible for Cushing syndrome during pregnancy and after menopause (Lacroix et al 1999), vasopressin, catecholamines, serotonin 5-HT, angiotensin II (ang II) and glucagon (Imöhl et al 2002, Miyamura et al 2002, Lee et al 2005, Vezzosi et al 2007, Gagliardi et al 2009, Hofland et al 2013. The prevalence of such illegitimate membrane receptors in PBMAH is high, varying from 77% to 87% among studies , Hofland et al 2013.…”
Section: Primary Bilateral Macronodular Adrenal Hyperplasia (Pbmah)mentioning
confidence: 99%